A midgut‐specific serine protease, BmSP36, is involved in dietary protein digestion in the silkworm, Bombyx mori. (1st September 2016) - Liu, Hua‐Wei; Li, You‐Shan; Tang, Xin; Guo, Peng‐Chao; Wang, Dan‐Dan; Zhou, Chun‐Yan; Xia, Qing‐You; Zhao, Ping
Abstract: Serine proteases play important roles in digestion and immune responses during insect development. In the present study, the serine protease gene BmSP36, which encodes a 292‐residue protein, was cloned from the midgut cells of Bombyx mori . BmSP36 contains an intact catalytic triad (H57, D102 and S195) and a conserved substrate‐binding site (G189, H216 and G226), suggesting that it is a serine protease with chymotrypsin‐like specificity. The temporal and spatial expression patterns of BmSP36 indicated that its messenger RNA and protein expression mainly occurred in the midgut at the feeding stages. Western blotting, immunofluorescence and liquid chromatography‐tandem mass spectrometry analyses revealed secretion of BmSP36 protein from epithelial cells into the midgut lumen. The transcriptional and translational expression of BmSP36 was down‐regulated after starvation but up‐regulated after refeeding. Moreover, expression of the BmSP36 gene could be up‐regulated by a juvenile hormone analogue. These results enable us to better define the potential role of BmSP36 in dietary protein digestion at the feeding stages during larval development.